PENGARUH KEPEMIMPINAN LURAH TERHADAP PARTISIPASI MASYARAKAT DALAM PERENCANAAN PEMBANGUNAN DI KELURAHAN PADANG BULAN KECAMATAN MEDAN BARU KOTA MEDAN - Denis Pramoedyo; Sally Marisa Sihombing (Smart Education, 2023)
Community Leadership and Participation have important values in Development Planning. This study aims to determine the effect of village head leadership on community participation in development planning in Padang Bulan Village, Medan Baru District, Medan City. The type of research used is associative research using quantitative data analysis. The population that was sampled in this study was the people who were recorded as residents of the Padang Bulan Village, Medan Baru District, Medan City, amounting to 98 people. This research instrument uses a questionnaire with Likert scale measurements whose data will be processed by Structural Equation Modeling (SEM) analysis in the Smart Partial Least Square (SmartPLS) program, which consists of two models, namely, the measurement model (outer model) and structural model (inner model). The results showed that the leadership at the Padang Bulan Sub-District Office, Medan Baru District, Medan City was in the very high category. Community participation in development planning in the Padang Bulan sub-district, Medan Baru sub-district, Medan City is in the high category. The coefficient of determination (R Square) is 0.899 indicating the magnitude of the influence of leadership on community participation in development planning is 89.9% and the remaining 10.1% is influenced by other variables outside of this research. These results indicate that leadership has a positive and significant effect on community participation in development planning in Padang Bulan Village, Medan Baru Subdistrict, Medan City, where if leadership increases, community participation in development planning will also increase in Padang Bulan Village, Medan Baru Subdistrict, Medan City.